2010
DOI: 10.1155/2010/248321
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypoadiponectinemia with Hypoglutathionemia in NAFLD Subjects with and without Type 2 Diabetes

Abstract: Abstract.Objective: The aim of this study is to measure the extent of oxidative stress and to see whether it has any correlation to changes in adiponectin levels in NAFLD subjects with and without Type 2 diabetes. Methods: Subjects recruited from the Chennai Urban Rural Epidemiology Study comprise of 1: Normal Glucose Tolerance (NGT) subjects without NAFLD; 2: NGT with NAFLD; 3: Type 2 Diabetic patients [T2DM] without NAFLD and 4: T2DM with NAFLD. Thiobarbituric acid reactive substances (TBARS), protein carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…An inverse correlation between adiponectin and the ratio of GSSG/GSH was found in 12 obese psoriasis patients () and similarly adiponectin correlated positively with the GSG/GSSG ratio in 120 subjects with or without diabetes and with or without nonalcoholic fatty liver disease (). Further, adiponectin was shown to restore the GSH/GSSG ratio after it was reduced when treating HepG2 cells with palmitate (). We did not find a significant association with the GSH/GSSG ratio, but a strong association with the absolute levels of GSH and TGSH.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An inverse correlation between adiponectin and the ratio of GSSG/GSH was found in 12 obese psoriasis patients () and similarly adiponectin correlated positively with the GSG/GSSG ratio in 120 subjects with or without diabetes and with or without nonalcoholic fatty liver disease (). Further, adiponectin was shown to restore the GSH/GSSG ratio after it was reduced when treating HepG2 cells with palmitate (). We did not find a significant association with the GSH/GSSG ratio, but a strong association with the absolute levels of GSH and TGSH.…”
Section: Discussionmentioning
confidence: 97%
“…Some previous studies, mostly in smaller and/or selected study samples, have shown an association between adiponectin and pro‐ and anti‐oxidative markers (). The association between adiponectin and glutathione (GSH) remains to be fully elucidated, but an association between adiponectin and the ratio of oxidized and reduced GSH has been suggested (). An inverse correlation between adiponectin and measures of lipid peroxidation has been reported in some studies (), but not all ().…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in accordance with previous studies in both western and Asian populations. [14][15][16] Adiponectin concentrations are 20-60% lower in patients with NAFLD than in healthy persons. 17 The present study indicates that 80% of the DFL patients and 72% of subjects of NDFL group have BMI >25 kg/m 2 and 80% of subjects in the DFL group and 68% of the subjects in the NDFL group have a waist circumference that indicates central obesity as per Asian cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD was also shown to be associated with hypoglutathionemia and hypoadiponectinemia. 26 NAFLD and other insulin-resistant states are associated with activation of the innate immune system, resulting in chronic subclinical inflammation. 27 Some studies have documented a significant association between leukocyte count and the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%